Assessment of Liver Stiffness in Pediatric Fontan Patients Using Transient Elastography. (30th August 2016) - Chen, Becky; Schreiber, Richard A.; Human, Derek G.; Potts, James E.; Guttman, Orlee R.
Abstract : Background . Hepatic fibrosis is a potential complication following Fontan surgery and heralds long-term risk for cirrhosis. Transient elastography (TE) is a rapid, noninvasive method to assess liver fibrosis by measuring liver stiffness. Objectives . To compare liver stiffness and liver biochemistries in pediatric Fontan patients with age- and sex-matched controls and to determine patients' acceptance of TE. Methods . Patients were recruited from British Columbia Children's Hospital. Twenty-two Fontan patients (15 males) were identified. Demographic information and cardiac data were collected. TE was measured using size-appropriate probes. Results . The median age of the Fontan cohort was 13.7 (5.9–16.8) years. Time from Fontan surgery to TE was 9.6 (1.0–12.9) years. The median Fontan circuit pressure was 13 (11–14) mmHg. TE values were higher in Fontan patients versus controls (18.6 versus 4.7 kPa, p < 0.001 ). There was no association between TE values and patient age (r = 0.41, p = 0.058 ), time since Fontan surgery (r = 0.40, p = 0.062 ), or median Fontan circuit pressure (CVP) (r = 0.35, p = 0.111 ). Patients found TE to be nonpainful, convenient, and safe. Conclusions . TE is feasible to assess liver stiffness in children following Fontan surgery. Pediatric Fontan patients have markedly elevated liver stiffness values. TE may have important utility in liver care follow-up of pediatric Fontan patients.